Studying process in a Title IV-E waiver evaluation project: Interviews with regional and executive managers. Issue 1 (1st January 2019) - Bloomquist, Kori R.; Imburgia, Teresa M.; Danh, Marie; Pierce, Barbara; Hall, James A.
ABSTRACT: A Midwestern state's child welfare agency contracted with a university to evaluate a 5-year Title IV-E Waiver Demonstration Project. As part of the process study, evaluators employed case study analysis to investigate Waiver knowledge and effects as reported by Regional and Executive Managers across 4 years of the demonstration period. Data from 78 interviews reveal enhanced levels of manager–evaluator rapport and integrated Waiver knowledge across years of data collection. This study highlights the value of middle managers as rich data sources, studying process through qualitative methods in child welfare evaluation, and how consistent relationships can support partnerships over time.